A case for institutional investigations in economic research methods with reference to South Africa's agricultural sector - Mbatha, Cyril (Rhodes University, Faculty of Commerce, Department of Economics, 2008)
Economic development remains elusive for many world economies, but especially those of African countries. The current global inequalities in terms of GNP per capita and human living standards between developed and developing nations have ensured that the challenges of food insecurities are only some of the many negative experiences of underdevelopment in the African continent. Hence, delivery pressures are increasing on policy makers and researchers to provide tangible and timely economic solutions to the resilient state of underdevelopment. In the policy fights against the challenges posed by a lack of development in South Africa, the agricultural sector has in the past and continues in the present to play a central role. Such is the case because the majority of citizens rely on agricultural production activities for their livelihoods. For instance, even though the sector only contributed four percent towards the national Gross Domestic Product in 2006, in the Eastern Cape Province, more than seventy percent of the total population resided in rural areas. Moreover, in 2004 more than sixty percent of the national formal and informal employment levels were found in the sector. These economic indicators do not only reinforce the assertions that high levels of geographical and sectoral inequalities exist in the country's economy, but they also illustrate the importance of the agricultural sector in public policy attempts, which are aimed at achieving food security alongside long-term developmental objectives. Some economists, especially the proponents of institutionalism, have argued that most of the recommendations to public policy interventions from mainstream economic research endeavours are not adequately helpful. The recommendations generally lack well considered and socially effective ideas, mainly because there remains some level of ignorance about the impacts that institutions have on economic and social systems. Some argue that this ignorance is reflected in (flawed) hedonistic and rationalist assumptions made about economic actors and in the methodological thinking of many research designs and economic analyses. The misuse of formal tools and statistical methods, for example, are some of the important factors, which have led to failures of the discipline of economics to provide effective policy solutions to problems of underdevelopment and poverty, especially in poor country environments. The thesis, having taken account of the majority of criticisms levelled against the classical and new-classical economic schools of thought, argues that the discipline as a whole lacks a paradigmatic integration of institutional and new-classical economic perspectives to offer appropriate guidelines for a methodology aimed at achieving socially responsive research outputs. The lack of this integration has resulted in a skewed selection of methods by economists, which are employed in research without a supportive and in-depth understanding of institutional and social factors. To support the thesis, a more effective and integrated framework for economic research is developed and presented with case study illustrations in a cumulative manner. The 20th century history of agricultural policies in South Africa, the agricultural and institutional case studies from the Eastern Cape Province alongside reviews of other agricultural studies are all used in presenting a case for rigorous institutional investigations in general economic research. These are also used in developing the proposed integrated framework, which aims to give guidance in developing research methods, which are more socially responsive. Having shown the usefulness of the proposed research framework, the thesis recommends that public policy interventions (at national and local levels) should aim to eliminate all types of institutions which have high associated transactional costs. The interventions should also encourage the emergence and growth of the types of institutions, which present the lowest costs to initiatives of economic development. In the primary case studies from the Eastern Cape Province, the insecurity of land tenure and the various local initiatives of business ventures are highlighted as two examples of the types of institutions, which respectively present high and low transactional costs to local initiatives of agricultural and economic development.
Keywords: Economic development -- South Africa; Economic development -- Research -- Methodology; Agriculture -- South Africa; Agriculture -- Economic aspects -- South Africa; Agricultural productivity -- South Africa; Agriculture -- Research -- South Africa; South Africa -- Economic conditions